A literature review of herpes simplex virus hepatitis in pregnancy. (18th May 2020) - Magawa, Shoichi; Tanaka, Hiroaki; Furuhashi, Fumi; Maki, Shintaro; Nii, Masafumi; Toriyabe, Kuniaki; Ikeda, Tomoaki
Abstract: Purpose: Hepatitis due to herpes simplex virus (HSV) during pregnancy is rare, it is often not included in the differential disease. However, hepatitis leads to maternal death; hence, early diagnosis is necessary. Hepatic enzyme elevation in late pregnancy is often associated with obstetric-related diseases, such as acute gestational fatty liver and HELLP syndrome (hemolytic anemia, elevated liver enzymes, low platelet count). These pregnancy-related diseases often improve maternal condition after completion of pregnancy, but in patients with HSV hepatitis, invasive treatment, such as cesarean section, may lead to deterioration of maternal condition after completion of pregnancy. A systematic review was conducted to extract necessary factors to avoid maternal death caused by herpetic hepatitis. Methods: In 24 cases reported since 1991, age, onset gestational weeks, initial symptoms, days from onset of symptoms to consultation, diagnosis method, treatment method, maximum liver escape enzyme value during hospitalization, bilirubin value, international normalized ratio value, and fetal/neonatal prognosis were extracted, and the relationship between maternal death group ( n = 6) and maternal alive group ( n = 18) was statistically analyzed. Results: Fever as an initial symptom was observed in all cases. Maternal death did not occur in patients administered with acyclovir (ACV) as empiric therapy. No difference was found between the two groups in other factors. Conclusion: Early diagnosis and treatment of herpetic hepatitis during pregnancy are important, as well as administration of empiric ACV concurrently with noninvasive diagnosis when a pregnant woman has elevated liver enzyme accompanied by fever in late pregnancy.